Nutrition and education in childhood: is it possible to show a causal relationship using cross-section data? - Rabassa, Mariano (2003)
The fact that nutrition affects education outcomes is accepted by researchers and by policy makers. It is simple. Children cannot learn if they are hungry. The validity of the empirical approaches used to show a causal relationship from nutrition to education is an issue of debate. The presence of unobserved characteristics that influence both variables is the main concern of researchers. The goal of this paper is to study the possibility of overcoming these difficulties using the NHANES III (1988-1994), a cross-section data set with national representation in the US. A set of school outcomes and a dummy that accounts for the "food-insecurity" condition of each child's family are the central variables here. Based on a IVs procedure, it looks for variables that can be used as instruments for the "food-insecurity" condition. The preliminary results indicate that child's height and mother's body mass index are no good instruments to do so. Further research in needed to construct other variables that might turn to be good instruments for food-insecurity.